LEGAL IMPLICATIONS OF INTEGRATING ISLAMIC LAW IN HIGH SCHOOL CURRICULUM: A STUDY OF OUTDOOR LEARNING MODELS AND P5 - Ikchsan, Nur; Kholifah, Siti; Hari Prasetyo, Fajar (fakultas hukum universitas PGRI Semarang, 2024)
This study aims to address the suboptimal learning outcomes observed in Islamic law education among students of class X-9 at State Senior High School 9 Semarang, where a significant number of students scored below the Minimum Completeness Criteria (KKTP) threshold of 75. The research focuses on improving these outcomes by employing a novel pedagogical approach, integrating the heuristic learning model with the Pancasila Student Profile Strengthening Project (P5). The study was conducted in three phases: Pre-cycle, Cycle I, and Cycle II. Initial findings in the Pre-cycle indicated that only 14 students (38.89%) met the KKTP standards. Following the introduction of the heuristic learning model in Cycle I, this number increased to 24 students (66.67%). However, since the desired success threshold was not fully achieved, Cycle II was implemented, resulting in a significant improvement, with 32 students (88.89%) successfully meeting the KKTP criteria. These findings suggest that the integration of heuristic learning strategies with the P5 initiative positively impacts students' learning outcomes in Islamic law education.